Gandhi - Attenborough, Richard; Briley, John, 1940-; Shankar, Ravi, 1920-2012; Indo-British Films, Ltd.; International Film Investors (Firm); Goldcrest Films International; National Film Development Corporation of India; LC Purchase Collection (Library of Congress) ([Mumbai : Marketed by National Education & Information Films Limited : Distributed by Diskovery Video & Laser Co. Pvt. Ltd., 2006)
Feature film on Mahatma Gandhi, 1869-1948 stressing his philosophy of nonviolence as a technique for political change, from his activities in Southern Africa in the Indian Congress Party (1893) through his return to India (1915), his role in the Indian National Congress Party, and his various campaigns and struggles for Indian independence. Ends with his death by assassination in 1948, just a few months after Indian independence.
Copyright notice on disc cover: Diskovery Video & Laser Co. Pvt. Ltd.
Associate producer, Suresh Jindal ; sound recordist, Simon Kaye ; 2nd unit director/cameraman, Govind Nihalani ; production designer, Stuart Craig ; editor, John Bloom ; co-producer, Rani Dube.
Ben Kingsley, Candice Bergen, Edward Fox, John Gielgud, Trevor Howard, John Mills, Martin Sheen, Rohini Hattangady.
English and Hindi.
Originally released theatrically in 1982.
Summary from Internet movie database, Oct. 16, 2009.
Keywords: Gandhi, -- Mahatma, -- 1869-1948 -- Drama; Nonviolence -- Drama; India -- Politics and government -- 1919-1947 -- Drama; Feature films; Fiction films; Biographical films